CD44-targeting hydrophobic phosphorylated gemcitabine prodrug nanotherapeutics augment lung cancer therapy. (June 2022) - Guo, Beibei; Wei, Jingjing; Wang, Jingyi; Sun, Yinping; Yuan, Jiandong; Zhong, Zhiyuan; Meng, Fenghua
Abstract: Gemcitabine (GEM) is among the most used chemotherapies for advanced malignancies including non-small cell lung cancer. The clinical efficacy of GEM is, however, downplayed by its poor bioavailability, short half-life, drug resistance, and dose-limiting toxicities (e.g. myelosuppression). In spite of many approaches exploited to improve the efficacy and safety of GEM, limited success was achieved. The short A6 peptide (sequence: Ac-KPSSPPEE-NH2 ) is clinically validated for specific binding to CD44 on metastatic tumors. Here, we designed a robust and CD44-specific GEM nanotherapeutics by encapsulating hydrophobic phosphorylated gemcitabine prodrug (HPG) into the core of A6 peptide-functionalized disulfide-crosslinked micelles (A6-mHPG), which exhibited reduction-triggered HPG release and specific targetability to CD44 overexpressing tumor cells. Interestingly, A6 greatly enhanced the internalization and inhibitory activity of micellar HPG (mHPG) in CD44 positive A549 cells, and increased its accumulation in A549 cancerous lung, leading to potent repression of orthotopic tumor growth, depleted toxicity, and marked survival benefits compared to free HPG and mHPG (median survival time: 59 days versus 30 and 45 days, respectively). The targeted delivery of gemcitabine prodrug with disulfide-crosslinked biodegradable micelles appears to be a highly appealing strategy to boost gemcitabine therapy for advance tumors. Statement of significance: Gemcitabine (GEM) though widely used in clinics for treating advanced tumors is associated with poor bioavailability, short half-life and dose-limiting toxicities. Development of clinically translatable GEM formulations to improve its anti-tumor efficacy and safety is of great interest. Here, we report on CD44-targeting GEM nanotherapeutics obtained by encapsulating hydrophobic phosphorylated GEM prodrug (HPG), a single isomer of NUC-1031, into A6 peptide-functionalized disulfide-crosslinked micelles (A6-mHPG). A6-mHPG demonstrates stability against degradation,  enhanced internalization and inhibition toward CD44 +  cells, and increased accumulation in A549 lung tumor xenografts, leading to potent repression of orthotopic tumor growth, depleted toxicity and marked survival benefits. The targeted delivery of GEM prodrug using A6-mHPG is a highly appealing strategy to GEM cancer therapy. Graphical abstract: Image, graphical abstract